2015
DOI: 10.1074/jbc.m114.588236
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ORMDLS, Modulators of Serine Palmitoyltransferase, Is Regulated by Sphingolipids in Mammalian Cells

Abstract: Background:In contrast to their yeast orthologues, the mechanism by which mammalian ORMDLs regulate serine palmitoyltransferase is not understood. Results: Overexpression of serine palmitoyltransferase in HEK293 cells results in increased long-chain base synthesis and an activity-dependent increase in ORMDL expression. Conclusion: A product of ceramide synthase mediates regulation of ORMDL expression and inhibition of serine palmitoyltransferase. Significance: Serine palmitoyltransferase activity indirectly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
(42 reference statements)
5
44
1
Order By: Relevance
“…This result confi rms that while at endogenous levels of SPT, ORMDL levels are suffi cient to control SPT activity; elevation of SPT upsets that ratio, which is corrected by overexpression of ORMDL3 . Similar results have recently been reported in HEK293 cells ( 19 ). Changes in levels of sphingosine do not follow the pattern of the other sphingolipids, being reduced by SPT overexpression.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This result confi rms that while at endogenous levels of SPT, ORMDL levels are suffi cient to control SPT activity; elevation of SPT upsets that ratio, which is corrected by overexpression of ORMDL3 . Similar results have recently been reported in HEK293 cells ( 19 ). Changes in levels of sphingosine do not follow the pattern of the other sphingolipids, being reduced by SPT overexpression.…”
Section: Resultssupporting
confidence: 89%
“…3C ). This may refl ect a difference in endogenous levels of ORMDLs in the HeLa cells used in the experiments reported here and the HEK293 cells utilized by Gupta et al ( 19 ). Alternatively the timing and levels of SPT expression may be important for the effect of SPT expression on ORMDL levels.…”
Section: Low-level Ormdl3 Overexpression In Airway Epithelial Cells Rmentioning
confidence: 89%
See 1 more Smart Citation
“…These findings suggested that yeast ORM proteins are negative regulators of sphingolipid biosynthesis and act through the inhibition of SPT. This conclusion was later confirmed in other studies using cells of various origin, including rice (66), mice (67), and human cell lines (68)(69)(70)(71).…”
Section: -Ketodihydrosphinganine Reductasesupporting
confidence: 67%
“…The fact that expression of hLCB1 did not change after increased SPT activity indicates that autoregulation of SPT expression is not a major mechanism for the regulation of sphingolipid biosynthesis. It was also shown that the main signal to induce ORMDL expression comes from ceramides rather than long-chain bases (69).…”
Section: The Role Of Ormdls In Immune Response Regulationmentioning
confidence: 99%